Personal traits and formalization of entrepreneurial ventures: insights from a developing country - Kasimu Sendawula; Shamirah Najjinda; Marion Nanyanzi; Saadat Nakyejwe Lubowa Kimuli; Ahmad Walugembe (New England Journal of Entrepreneurship)
Purpose – The purpose of this study is to explore how the personal traits of the informal entrepreneurs influence their formalization decisions. Design/methodology/approach – This study adopted a qualitative approach using a multicase design in which 28 informal entrepreneurs situated in Kampala district, Uganda, were engaged. An interview guide, recorders and note books were used in data collection. Findings – The results indicate that the traits of informal and semiformal entrepreneurs are distinct. Informal entrepreneurs have been noted to be more courageous and resilient, while their semiformal counterparts have greater passion for their businesses. It is thus observed that the formalization prospects are higher for the semiformal entrepreneurs than for their informal counterparts. Entrepreneurs that would be willing to formalize their businesses are discouraged by distance, technology and the cost of involving middlemen. Whereas the resilient entrepreneurs are noted to work through these challenges, the passive ones in both the informal and semiformal categories will not formalize their businesses by giving such excuses. Originality/value – This study contributes to the extant literature on informal entrepreneurship by providing initial empirical evidence on how the personal traits of the entrepreneurs influence their formalization decisions specifically.